Prospects of Technology Adoption in Small Pump Schemes in the River Nile State, Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
Linear programming was used to simulate the farming systemsof small pump schemes in Shendi area, River Nile State, Sudan, to assessthe prospects for technology use in cool-season food legumes and wheat.Different production activities, with respect to target crops, wereidentified to reflect different technology levels. The model constraintswere the pump capacity, the scheme size and family labour. Alternativeversions of the model were developed to examine possible productionoptions that exist and to examine the effects of alternative resource levelsand policy options, which are likely to affect adoption. The model resultsrevealed that while farmers' traditional practices were not economicallyfeasible options, tendency is for adoption of medium rather than therecommended high technology levels. This reflects actual farmers'behaviour, particularly for irrigation water, and indicates that water is themain resource constraint. The results also showed that the technology isnot well supported by the traditional institutions of production relations,which create conflicting perception between resource owners towardstechnology use.
Keywords: Pump schemes; linear programming; food legumes; wheat; adoption